2010
DOI: 10.1111/j.1468-0297.2010.02364.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Class Size Effects: New Evidence from a Panel of University Students

Abstract: Over the last decade, many countries have experienced dramatic increases in university enrolment, which, when not matched by compensating increases in other inputs, have resulted in larger class sizes. Using administrative records from a leading UK university, we present evidence on the effects of class size on students' test scores. We observe the same student and faculty members being exposed to a wide range of class sizes from less than 10 to over 200. We therefore estimate non-linear class size effects con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(122 citation statements)
references
References 49 publications
6
113
0
3
Order By: Relevance
“…The treatment causes an increase in total grade points by about 0.30 standard deviations in this group, where these students both complete more courses and improve their grade average. To put the size of the main effect in context, we note that it is comparable to the effect of: a one standard deviation improvement in teacher quality (Rockoff, 2004); a one standard deviation in university class size (Bandiera et al, 2010); and substantial individual incentives for academic performance in college (Angrist et al, 2009), which all have been shown to improve academic performance by about 0.15 standard deviations.…”
Section: Resultsmentioning
confidence: 99%
“…The treatment causes an increase in total grade points by about 0.30 standard deviations in this group, where these students both complete more courses and improve their grade average. To put the size of the main effect in context, we note that it is comparable to the effect of: a one standard deviation improvement in teacher quality (Rockoff, 2004); a one standard deviation in university class size (Bandiera et al, 2010); and substantial individual incentives for academic performance in college (Angrist et al, 2009), which all have been shown to improve academic performance by about 0.15 standard deviations.…”
Section: Resultsmentioning
confidence: 99%
“…Minimal cost to conduct the study. 3 Simple procedure that any instructor can use. 4 Permits use of a true experimental design using archival data.…”
Section: Discussionmentioning
confidence: 99%
“…7 As argued by Bandiera, Larcinese and Rasul (2008) focusing on this kind of measure is particularly relevant for policy implications, since the official class size can be modified by universities, while interventions aimed at regulating the physical attendance of students may be much more complex.…”
Section: As Shown Inmentioning
confidence: 99%
“…A recent study by Bandiera, Larcinese and Rasul (2008) investigates the effects produced by these opposing forces by analysing class size effects on college student performance. Using data from a leading UK university, they show a negative and significant effect of class size for the smallest and largest ranges of class size, while the effect for intermediate class sizes (from 33 to 104 students) is not significantly different from zero.…”
Section: Introductionmentioning
confidence: 99%